2020
DOI: 10.1002/anie.202007147
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Dehydroaromatization over Ga‐ZSM‐5 Catalysts: Nature and Role of Gallium Speciation

Abstract: Bifunctional catalysis in zeolites possessing both Brønsted and Lewis acid sites offers unique opportunities to tailor shape selectivity and enhance catalyst performance. Here,w ee xamine the impact of framework and extra-framework gallium species on enriched aromatics production in zeolite ZSM-5. We compare three distinct methods of preparing Ga-ZSM-5 and reveal direct (single step) synthesis leads to optimal catalysts compared to post-synthesis methods.U sing ac ombination of state-of-the-art characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 60 publications
(6 reference statements)
3
32
0
Order By: Relevance
“…It was found that such a high dispersion of Ga facilitated the formation of active gallium species, which have a good synergism with Brønsted acid sites. 250,251 Lin et al prepared a series of nanosized [Al]-, [Ga, Al]-, and [Ga]-HZSM-5 catalysts with a fixed Si-to-M 3+ ratio (M = Al or Ga) via the direct hydrothermal synthesis method. 43 Among all tested catalysts, [Ga, Al]HZSM-5 with a total Ga/Al ratio of 0.5 but a low extra-framework Ga-to-Brønsted acid ratio of 0.06, was found to be the most effective in the methanol aromatization, exhibiting an initial aromatic selectivity of 79.5% at 500 °C.…”
Section: Methanol-to-aromaticsmentioning
confidence: 93%
“…It was found that such a high dispersion of Ga facilitated the formation of active gallium species, which have a good synergism with Brønsted acid sites. 250,251 Lin et al prepared a series of nanosized [Al]-, [Ga, Al]-, and [Ga]-HZSM-5 catalysts with a fixed Si-to-M 3+ ratio (M = Al or Ga) via the direct hydrothermal synthesis method. 43 Among all tested catalysts, [Ga, Al]HZSM-5 with a total Ga/Al ratio of 0.5 but a low extra-framework Ga-to-Brønsted acid ratio of 0.06, was found to be the most effective in the methanol aromatization, exhibiting an initial aromatic selectivity of 79.5% at 500 °C.…”
Section: Methanol-to-aromaticsmentioning
confidence: 93%
“…The XPS spectra for the reduced catalyst in the Ga 2p 3/2 region show a loss of peak intensity, indicating the high dispersion of the metal species on the zeolite surface. For the red-Ga and red-GaPt catalysts, the intensity loss indicates the penetration of the Ga species into the zeolite pores and ion exchange of the metal promotors with the Brønsted acid sites. ,, XPS of the red-Ga and red-GaPt catalysts exhibited a shift in speciation to the higher binding energy of 1120.0 eV. The shift to the higher binding energy when compared to those of the fresh catalysts indicates the increased presence of Ga + and/or GaO + on the external surface following the reduction of the catalyst.…”
Section: Resultsmentioning
confidence: 98%
“…17,18,35,37 Specifically, it has been shown for Gamodified ZSM-5 that the intrazeolite Ga species of the catalyst can dehydrogenate ethane to form ethylene, which then can be further oligomerized and aromatized by the Ga Lewis acid sites species and the Brønsted acid sites. 35,37,38 In this work, further investigation of the synergistic effects of the bimetallic GaPt promoted ZSM-5 catalyst was performed. The effectiveness of the hydrogen pretreatment of gallium and platinum promoted ZSM-5 was tested for the ethane dehydroaromatization reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the roles of Ga in the reaction system, it is one of the most efficient catalyst components for olefin aromatization, and it also catalyzes conversions of light alkanes such as propane and butanes to aromatics. The Cyclar process is an example of this application.…”
Section: Discussion and Comparison Between One-step And Two-stepmentioning
confidence: 99%